Magnetic resonance spectroscopy and diffusion contrast imaging in differentiating recurrence of primary brain tumors - Mousavizadeh, Bahareh; Faeghi, Fariborz; Tabatabai, Mehdi (Researcher Bulletin of Medical Sciences, 2025)
Objective: Differentiation of brain tumor recurrence from necrosis caused by radiation after radiotherapy is often considered a radiological ambiguity. The purpose of this study is to investigate the effectiveness of magnetic resonance spectroscopy in differentiating the recurrence of primary brain tumors (glioma) from necrosis caused by radiation. Materials and Methods: 15 patients (with an average age of 40.07, 8 men and seven women) were examined in this study. The samples of this study were selected from patients who have already been confirmed to have a glioma brain tumor and requested radiotherapy. 12 weeks (or three months) after radiotherapy, MRS imaging sequences with CSI technique and DWI imaging sequence with b-value=1000 s/mm2 were performed for all patients, and metabolic coefficients and quantitative ADC maps were also obtained. Then, the average ADC value and metabolic ratios were calculated for all patients. Results: The pathological and clinical results of the patients were compared with the results of MRS and DWI. By analyzing the ROC curve on the data obtained from the two techniques implemented in this study, it shows that the area under the ROC curve for ADC maps was higher than that of the MRS technique, which shows that the results of DWI can reliably diagnose and differentiate tumor recurrence from radiotherapy necrosis. Also, the result of this study showed that tumor recurrence has a significantly lower ADC compared to radiotherapy necrosis (p=0.035). Conclusion: The results of MRS indicates that the metabolic ratios of Cho/NAA and Cho/Cr are higher in people who have had tumor recurrence than in people in whom necrosis from radiotherapy has been reported. DWI images obtained with b-value = 1000 s/mm2 provide more reliable results than MRS images with the CSI technique and are considered a valuable tool in differentiating tumor recurrence from radiotherapy necrosis; the reliability of both imaging results increases, and the ability to detect tumor recurrence from necrosis caused by radiotherapy